Immunity to change how to overcome it and unlock potential in yourself and your organization - Kegan, Robert (Boston, Mass. Harvard Business Press, 2009)
A recent study showed that when doctors tell heart patients they will die if they don't change their habits, only one in seven will be able to follow through successfully. Desire and motivation aren't enough: even when it's literally a matter of life or death, the ability to change remains maddeningly elusive.
Includes bibliographical references and index.
Keywords: Organizational change